Superconductivity and X-Ray Crystallographic Structures of LaxBa1+xCu1+2xOy (x = 2, 3, ...) - Wook Lee, Sung; Won Lee, Jung; Jun Won, Hui; Kim, Don; Yang Chung, Won (Asian Journal of Chemistry, 2012)
In present study, the thermal analysis, Rietveld refinement, magnetic susceptibility and electrical resistivity of LaxBa1+xCu1+2xOy (x = 2, 3, ...) have been reported. It is possible to interpret the relationship between the crystal structures and the superconductivity. All the compounds have tetragonal structure with triple perovskite unit. A portion of La atoms occupied Ba site and more La atoms were in the Ba site as the composition of La increased. The oxygen atoms at the pyramid base responsible for the superconductivity migrated to vacancies around Ba site to neutralize the excess positive charge of La3+ ions. La-336 compound, which is the ultimate composition of the series, loses superconductivity as a result of pyramid collapse.